Facile method for the synthesis of Co-core Au-shell nanohybrid - Sardar, Debasmita; Neogi, S. K.; Bandyopadhyay, Sanjoy; Satpati, Biswarup; Jain, Ruchi; Gopinath, Chinnakonda S.; Bala, Tanushree (New Journal Of Chemistry, 2014)
Heterostructured Co-Au core-shell nanoparticles have been synthesized by reducing AuCl4- ions on cobalt nanoparticles after a minor but effective modification of cobalt surface by an amine. The core shell morphology is emphatically confirmed by thorough investigation through UV-Vis spectroscopy, X-ray photoelectron spectroscopy (XPS), and transmission electron microscopic analysis (TEM). The chemical composition and topography were determined using STEM-HAADF analysis and EFTEM imaging. Fourier transform infrared (FTIR) spectroscopy confirms the surface modification of Co nanoparticles and the interactions involved between the ligands and the core and shell metals at various steps of the synthetic process. The magnetic properties confirm the material to be superparamagnetic in nature.

Preferential growth of Au on CdSe quantum dots using langmuir-blodgett technique - Das, Subhasis; Satpati, Biswarup; Chauhan, Himani; Deka, Sasanka; Gopinath, Chinnakonda S.; Bala, Tanushree (RSC Advances, 2014)
Oleyl amine capped CdSe quantum dots (QD) were synthesised by hot injection technique. These QDs formed a self-assembled monolayer on an aqueous subphase of a Langmuir-Blodgett (LB) trough. Here, in this report we introduced a simple but very efficient route to form a metal (Au)-QD hybrid nanostructure via the LB technique. In this method, the metal counterpart of the hybrid nanostructure could be deposited exclusively on one side of the QDs. The formation of stable monolayer of QDs was evidenced from a surface pressure-area (P-A) isotherm. The development of gold tip was confirmed and monitored by detailed TEM study on the monolayer deposited on TEM grids from the LB trough. Other characterizations like UV-Vis spectroscopy, FTIR, XPS and EDX also suggested the same. Oleyl amine was shown to act both as a reducing agent as well as a capping agent in this strategy.

Multifaceted core-shell nanoparticles: superparamagnetism and biocompatibility - Sardar, Debasmita; Neogi, S. K.; Bandyopadhyay, Sanjoy; Satpati, Biswarup; Ahir, Manisha; Adhikary, Arghya; Jain, Ruchi; Gopinath, Chinnakonda S.; Bala, Tanushree (New Journal of Chemistry, 2015)
NicoreAgshell nanoparticles were synthesized by redox transmetallation reaction. Reduction potential match was encouraging to attempt the synthesis of the NicoreAushell system too. However, it could be achieved only after an effective surface modification on the Ni-core. Thorough characterization (UV-Vis spectroscopy, fluorescence spectroscopy, XRD, XPS, FTIR, TEM, and EDX) proved the necessity of surface modification and the success of synthesis of both types of core-shell structures. The chemical composition and topography were determined using STEM-HAADF analysis and EFTEM imaging. Fourier transform infrared (FTIR) spectroscopy confirmed the surface modification of Ni nanoparticles and the interactions involved between the ligands and metals (in the core and/or the shell) at various steps of the synthetic process. Even after the formation of the noble metal shell, the magnetic core was found to retain its superparamagnetic nature. In addition, the Au-shell protected the core from aerial oxidation and decreased toxicity as compared to pristine Ni nanoparticles as observed by MTT assay on normal cells (PBMCs).

Exploration of magnetically separable Ag@AgxNiy core/graded-alloy-shell nanostructures - Kumar, Mukesh; Soni, Kiran; Satpati, Biswarup; Gopinath, Chinnakonda S.; Deka, Sasanka (Chemical Communications, 2016)
We report novel bimetallic Ag@AgxNiy core@graded-alloy-shell nanoparticles (CGAS NPs), i.e. single Ag core NPs shelled by an AgxNiy graded alloy and stabilized by the CTAB surfactant employing a novel synthesis method. These Ag@AgxNiy CGAS NPs demonstrated superior catalytic performance in the synthesis of biologically active 3-amino alkylated indoles under green conditions.

Seeding of Au on CdSe/CdS nanoplates using Langmuir-Blodgett technique - Das, Subhasis; Satpati, Biswarup; Chauhan, Himani; Deka, Sasanka; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S.; Bala, Tanushree (RSC Advances, 2016)
Oleyl amine capped CdSe/CdS nanoplates were synthesized by hot injection technique which formed a stable monolayer over both a water subphase and an aqueous HAuCl4 subphase using a Langmuir-Blodgett trough. Au islands were generated at the edge as well as on one specific surface of the flat nanoplates by exploiting the reducing capacity of oleyl amine to form Au nanoseeds from AuCl4- ions. The initial Au nanoseeds changed to a shell surrounding these nanoplates on prolonged exposure to the subphase containing the Au precursor. Monolayer of the hybrid structures was deposited onto suitable substrates for characterization by a number of different techniques and to study the photocatalytic activity. The same substrate with the monolayers could be re-used in several cycles of photocatalysis.

Deposition of Au nanoparticles inside porous CeO2 nanocubes using Langmuir-Blodgett technique - Das, Subhasis; Bhattacharjee, Gourab; Satpati, Biswarup; Kumar, Mukesh; Deka, Sasanka; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S.; Bala, Tanushree (New Journal of Chemistry, 2018)
Porous 3D CeO2 nanocubes were synthesized using hot injection technique. These nanocubes were able to form a stable monolayer over water and HAuCl4 subphase in Langmuir-Blodgett (LB) trough due to the presence of surface capped oleic acid and oleylamine. CeO2-Au nanocomposites were synthesized exploiting the ability of oleylamine to reduce AuCl4 ions to Au-0, via LB method. CeO2 nanocubes gave rise to excellent long-range assembly at air/water interface and gold nanoparticles were formed inside these porous nanocubes without disturbing this arrangement. The formation of a stable monolayer was evidenced from the surface pressure-area (P-A) isotherm. The development of Au nanoparticles was confirmed with great effort from a comprehensive study using UV-Vis spectroscopy, XRD, XPS, FTIR, TEM, STEM, EDX, tomography and chemical mapping.

Dexterous route for synthesis of hollow spherical ZnO and ZnO-Ag nanocomposite with superior photocatalytic ability - Maity, Jayeta; Bhattacharjee, Gourab; Satpati, Biswarup; Sardar, Debasmita; Ghosalya, Manoj Kumar; Bala, Tanushree (ChemistrySelect, 2019)
Hollow spherical ZnO and hollow ZnO-Ag nanocomposites with variable percentage of loading of Ag content were successfully fabricated through a novel, template free and easily reproducible route. Extensive characterizations were carried out using FTIR, XRD, XPS, BET, TEM and SEM. The hollow morphology of the particle and the composite encouraged a detailed photocatalysis study in comparison to solid commercial ZnO and the corresponding ZnO-Ag composite. The photocatalytic activity of the hollow particle and the composite was assessed monitoring the decolouration of methylene blue dye using UV-Vis absorption spectroscopic technique. An increased surface area for hollow morphology as compared to solid particles established a conspicuous boost in photocatalytic activity.
Keywords: excellent photocatalysis; synthesis; template free; ZnO hollow nanoparticles; ZnO-Ag nanocomposite